Modeling Narcissistic Personality and Object Relations with the Mediating Role of Defense Mechanisms - Gholami Zarch, Morteza; Taghvaei, Davoud; Pirani, Zabihollah (Journal of Adolescent and Youth Psychological Studies (JAYPS), 2024)
Objective: Narcissistic personality disorder is conceptualized by Kernberg as one of the levels of personality, characterized by an unstable identity and primitive defense mechanisms such as splitting. The present study aimed to explain narcissistic personality disorder based on primary object relations with the mediating role of defense mechanisms.Methods and Materials: This descriptive study was conducted using a correlational design. The statistical population included all students enrolled in universities in Qom city during the 2020-2021 academic year, from which 397 individuals were selected using a convenience sampling method. Participants completed the Narcissistic Personality Questionnaire, Object Relations Questionnaire, and Self-Concept Scale. Structural equation modeling was conducted using data obtained from the questionnaires.Findings: The results showed that object relations directly explained 63% and indirectly through defense mechanisms explained 25% of the narcissistic personality. In total, the estimation of the structural model, where object relations were the predictor variable and defense mechanisms were included as the mediating variable, indicated that this model explained 88% of the narcissistic personality.Conclusion: Therefore, it can be concluded that narcissistic personality is explained both directly and indirectly through defense mechanisms by object relations.